Characterization of selenium in UO2 spent nuclear fuel by micro X-ray absorption spectroscopy and its thermodynamic stability. Issue 10 (14th September 2015) - Curti, E.; Puranen, A.; Grolimund, D.; Jädernas, D.; Sheptyakov, D.; Mesbah, A.
Abstract : The long-lived fission product 79 Se is tightly bound to the UO2 lattice in spent nuclear fuel; it will thus be released only very slowly from a geological repository for radioactive waste. Abstract : Direct disposal of spent nuclear fuel (SNF) in deep geological formations is the preferred option for the final storage of nuclear waste in many countries. In order to assess to which extent radionuclides could be released to the environment, it is of great importance to understand how they are chemically bound in the waste matrix. This is particularly important for long-lived radionuclides such as 79 Se, 129 I, 14 C or 36 Cl, which form poorly sorbing anionic species in water and therefore migrate without significant retardation through argillaceous repository materials and host rocks. We present here X-ray absorption spectroscopic data providing evidence that in the investigated SNF samples selenium is directly bound to U atoms as Se(−ii ) (selenide) ion, probably replacing oxygen in the cubic UO2 lattice. This result is corroborated by a simple thermodynamic analysis, showing that selenide is the stable form of Se under reactor operation conditions. Because selenide is almost insoluble in water, our data indirectly explain the unexpectedly low release of Se in short-term aqueous leaching experiments, compared to iodine or cesium. These results have a direct impact on safety analyses for potential nuclear waste repository sites, as they justify assuming a small fractional release of selenium in performance assessment calculations.